Bilateral Endoscopic Medial Maxillectomy for Bilateral Inverted Papilloma - Satoru Kodama; Toshiaki Kawano; Masashi Suzuki (Case Reports in Otolaryngology)
Inverted papilloma (IP) is a benign tumor of the nasal cavity and paranasal sinuses that is unilateral in most cases. Bilateral IP, involving both sides of the nasal cavity and sinuses, is extremely rare. This paper describes a large IP that filled in both sides of the nasal cavity and sinuses, mimicking association with malignancy. The tumor was successfully treated by bilateral endoscopic medial maxillectomy (EMM). The patient is without evidence of the disease 24 months after surgery. If preoperative diagnosis does not confirm the association with malignancy in IP, endoscopic sinus surgery (ESS) should be selected, and ESS, including EMM, is a good first choice of the treatment for IP.